Research progress on the mechanism underlying the application of mesenchymal stem cells in the treatment of male infertility - Tian, Xingzhao; Zhang, Jingyi; Tang, Xinyi; Guo, Xinlei; Gong, Yanan; Yang, Fang; Dong, Liang; Yu, Xujun (Frontiers in Endocrinology, 2025)
Male infertility has become an increasingly prominent health issue worldwide. This review systematically evaluated the therapeutic application of different types of MSCs in various male infertility models. The therapeutic effects of MSCs are attributed to mechanisms such as in vivo and in vitro differentiation into germ cells, improved antioxidant capacity of testicular tissue, inhibited secretion of inflammatory factors and elevated anti-inflammatory level of testicular tissue, prevention of excessive apoptosis of testicular tissue cells, restoration of the normal secretion of sexual hormone levels in vivo, and regulation of sperm autophagy. Simultaneously, this study also emphasized on the latest progress in the research of MSC-Exos, with the discussion of its potential advantages over traditional MSC therapy. In addition, this review also elucidated challenges in the clinical translation of MSCs, including safety and standardization issues, as well as the necessity of conducting human clinical trials. On these basis, this research proposed corresponding improvement plans, such as developing engineered MSCs products, optimizing delivery methods and exploring combination therapies, which may provide potential reference for the clinical application of MSCs and MSC-Exos on a large scale.